The necessity of a lead person to monitor development stages of the DevOps pipeline - Betool Alnamlah; Sara Alshathry; Norah Alkassim; Nor Shahida Mohd Jamail (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The Development-to-Operations model, known as DevOps, refers to a framework that integrates the development and operation phases of organizational applications. DevOps bridges the gap between these two processes that traditionally prolonged the implementation of these applications. This framework aims at enhancing service delivery and releasing subsequent updates based on real-time customer feedback. Consumers in this modern era prefer tailor-made services, and a slight downtime from one supplier can quickly shift their preference to the company’s competitors. However, DevOps involves sophisticated coding activities, and there is a need for someone to oversee these processes to ensure developers are not overwhelmed. The objective of this survey is to clarify the significance of a lead person to monitor the DevOps pipeline and report any failure detected in each development stage. The study utilized meta-analysis of verified tertiary resources from other researchers that took a deep dive into the DevOps model and how it works towards organizational goals in various firms. All institutions involved in multiple business platforms should take advantage of new technologies to scale up their service delivery and net profit. If adopted and appropriately monitored, DevOps can revolutionize the capabilities of most business applications by minimizing downtimes and providing uninterrupted services.